Zika virus: a cause of concern in transplantation?. Issue 4 (August 2017) - Levi, Marilyn E.
Abstract : Purpose of review: Worldwide, the number of countries reporting Zika virus (ZKV) infection continues to increase. Although 80% of cases are asymptomatic, ZKV has been identified as a neurotropic virus associated with congenital microcephaly, Guillain-Barre' syndrome, and meningoencephalitis. Until recently, infection in transplant recipients has not been identified. This study will review the existing literature on ZKV infection, laboratory testing, and management in transplant recipients. Recent findings: Donor-derived transfusion of contaminated blood products and naturally occurring ZKV infections have been recently reported in solid organ and stem cell transplant recipients, ranging from asymptomatic infections to meningoencephalitis. Interpretation of diagnostic testing of ZKV is evolving, with prolonged viral shedding identified in blood, semen, and urine of unclear significance. Serologic testing may be associated with cross-reactivity with other flaviviridae, requiring plaque reduction neutralization testing for confirmation. Thus far, donor screening guidelines for transplantation have not been established. Summary: The study reviews the limited existing literature in transplant recipients infected with ZKV, available laboratory testing and management. Ultimately, guidelines are needed for donor screening from high-risk areas, interpretation of studies and management of infected patients to ensure safe transplantation.